The Effect of Product Quality and Customer Satisfaction on Customer Loyalty at Pempek 888 Taman Kenten Palembang Restaurant - Amrullah, Amrullah; Taviprawati, Ervina; Permatasari, Dinda (Jurnal Penelitian Pariwisata, 2022)
This study aims to determine product quality and satisfaction on customer loyalty. This research uses descriptive research with a quantitative approach and multiple regression analysis methods. The sampling technique uses accidental sampling. The population is all customers who come to Pempek 888 Taman Kenten Palembang Restaurant, while the total sample is 98 respondents based on the Slovin formula. The results showed that product quality and satisfaction partially had a significant effect on customer loyalty. It is hoped that Pempek 888 Taman Kenten Palembang Restaurant will continue to maintain and improve product quality from color, appearance, portion, shape, temperature, texture, aroma, level of maturity, and taste offered, up to the halal guarantee provided must be maintained and improved so that customers continue to feel satisfied and do not move to another place. Keywords: Product Quality, Customer Satisfaction, Customer Loyalty